O cotidiano escolar dos jovens na/da educação de jovens e adultos: compreensão dos (des)encontros entre juventudes e escola - Lima, Divanir Maria De (2017)
This work investigated the daily school life of young people in the Education of Young and Adults (EYA) from reading this daily life as a space reinvented by its practitioners. It was anchored in the interlocution between the studies in the daily life of youth in the EYA and their cultures and had as its main question: How does the construction of life in the school daily life in Youth and Adult Education contribute to the understanding of meetings and of the lack them between youth and school? It investigated the daily life of the youths of two classes of the final years of Elementary School in the Education of Young and Adults of a public school in the city of Arapiraca, in the rural area of Alagoas, between the years 2013 and 2015. It aimed to "Understand the processes of construction of the daily school life of young people in / Education of young people and adults and how these processes trigger the cultures in circularity in this daily life producing (dis) meetings between youth and school." Certeau (2011,2012), Pais (2003, 2006, 2007, 2012), Feixa (1994, 1999, 2004, 2011), Elias (2011), Alves (1998, 2001, 2002, 2003, 2015), Dauster; Tosta; (2012), Gill (1991, 1998, 2012, 2014), Geertz (2012), Di Pierro; Joia; Ribeiro (2001), Haddad; Di Pierro (1999, 2000), Fávero, Freitas (2011), among others. The methodological course was based on ethnography as a research method, using tools such as participant observation, ethnographic interviews, photographs and the use of some social networks. The data showed "tactics" materialized in the "events" from which emerged the (dis) meetings between youth and school. As an "ecological environment" that shelters different cultures, the construction of the school daily life of young people showed "events" that fulfilled the role of denying the youth space in the EYA – and thus perpetuating the disinvisibilization of these people – as well as built strategies that subverting the established order, were moving towards the recognition of youth cultures as the expressiveness of the young people who reconfigure the school and its practices. The ethnographic findings have brought to the surface of daily life, from the inventing practices of the feeling of not belonging to a place historically destined for adults, disagreements woven by threads that aligned the stereotype of the "without- generation" youth, the young under eighteen, and ones without a place "in the EYA, to promoting generational and cultural differences among students. Therefore, there were tactics that reinvent "the ways to be how and do" in the school, meetings between the youth groups and the school occurred in the events exchanged in the most diverse "systems", which gave meanings to school practices and to the relationships established between school content and the future plans of the young, confirming the school as the place of meeting with friends, with teachers and with learning, but also of escapees, silences, laughter, resistance, transgressions, of the multiple languages, in short, of the astute reinvention of the students and teachers in the EYA.